Liability Against Wedding Organizer Default - Naufal Syaughi Margono; Tutiek Retnowati (Faculty of Law, Merdeka University Surabaya, Indonesia, 2021)
Marriage is one of the human needs there are various kinds of ways for marriage, one of the most popular in the modern era is now using the services of a wedding organizer, pandamanda is one of the wedding organizer services that dares to offer rental prices for services at prices below the average price of wedding planners in general. However, at the time the implementation carried out by Pandamanda to the consumer was not in accordance with what was promised, when the date of the wedding had taken place it turned out that the food in the wedding ceremony was not available. The formulation of the problems contained in this study were: 1 ) What is the legal protection for the default act committed by the wedding organizer to the consumer? 2) What is the legal action taken by the consumer as a result of the default by the Wedding Oganizer? The objectives of this research are 1) To find out and analyze legal actions for default actions committed by the wedding planner 2) To find out and analyze legal actions taken by consumers due to default actions by the wedding planner. The results of this study is a party that defaults to consumers as regulated in article 1243 of the Civil Code which reads that compensation for costs, losses and interest due to failure to fulfill an agreement shall begin to be obliged if the debtor, although declared negligent to carry out the engagement.